S1 A New, Efficient Web-based Tool To Collect And Code Lifetime Job Histories In Large Population-based Studies: The Copd Project In The Uk Biobank Cohort. (10th November 2014) - De Matteis, S; Jarvis, D; Wheatley, M; Azhar, H; Young, A; Young, H; Rushton, L; Cullinan, P
Abstract : Introduction and objectives: The manual collection and coding of job histories is the standard method for assessing occupational exposure, but may be infeasible for large population-based studies such as the UK Biobank cohort. Our aim was to develop a new web-based tool to automatically collect and code individual lifetime job histories in the UK Biobank cohort for investigating the causes and burden of work-related COPD in the UK. Methods: UK Biobank is a population-based cohort of 502, 682 subjects, aged 40–69 years, recruited in 2006–2010. Baseline spirometry data, current employment and smoking histories were collected. We developed a job questionnaire based on the hierarchical structure of the standard occupational classification (SOC) 2000 to allow participants to automatically self-collect and code their lifetime job histories. The web-based prototype (www.imperial.ac.uk/biobank/questionnaire ) was pre-piloted in May–August 2013 among key job sectors using snowball sampling together with a feedback survey. Results: 171 subjects participated in both the pre-piloting and feedback survey. 91% completed the questionnaire in <20 min, 85% considered the instructions clear, and 80% found their job categories/titles easily. Overall, 96% judged the questionnaire to be clear and easy. A revised questionnaire has now been designed and will be accessible from different media including PCs/laptops, tablets and smart phones to encourage high response. A demonstration version will be made available to conference participants. Conclusions: Our web-based job questionnaire is an efficient new standard tool for collecting and automatically coding lifetime job histories in large population-based studies and is adaptable for use in many occupational and environmental health research projects.